Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Peningkatan Kinerja Karyawan Di PT. Bank Sumut Syariah KCP Stabat - Nurhayati, Yaumul Khair Afif, Khairunnisa (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
This study aims to determine training and work discipline on improving employee performance at PT. Bank SUMUT Syariah KCP Stabat either partially or simultaneously. This type of research is quantitative research that emphasizes numerical data (numbers) processed using inferential statistical methods (analyzing the relationship between variables by testing hypotheses). The data source for this research was obtained directly from the answers to the questionnaires distributed to the research respondents, namely employees of PT. Bank SUMUT Syariah KCP Stabat. The results of the study explain that there is a significant influence between training on improving employee performance at PT. Bank SUMUT Syariah KCP Stabat, this was obtained from the hypothesis test, namely the t test of the Training variable (X1) statistically showing a significance value of less than 0.05 or (0.001 <0.05) and tcount > ttable (4.258 > 2.17881) then there is the effect of variable X on variable Y. There is a significant influence between work discipline on improving employee performance at PT. Bank SUMUT Syariah KCP Stabat, this was obtained from the hypothesis test, namely the t test of the Work Discipline variable (X2) statistically showing a significance value of less than 0.05 or (0.002 <0.05) and tcount > ttable (3.919 > 2.17881 ) then there is the effect of variable X on variable Y. There is a significant influence between training and work discipline together on improving employee performance at PT. Bank SUMUT Syariah KCP Stabat, this was obtained from the hypothesis test, namely the f test, the value of Fcount was obtained 41.271 with a significance level of 0.00 because the significance value was less than 0.05 (0.000 <0.05) and the value of Fcount > Ftable (41.271 > 3 .81), then the independent variables simultaneously affect the dependent variable.